Case Series of Retinal Damage Caused by Laser Pointer: Laser Pointer Retinal Injury - Mousavi, Zeinab; Bagheri, Masood (Journal of Lasers in Medical Sciences, 2025)
Introduction: Laser pointers are commonly used in various settings, including presentations, lectures, entertainment events, and toy applications. Although they have become increasingly popular, the misuse or accidental exposure to high-powered laser pointers can cause serious ocular injuries, including retinal damage. Methods: In this case series, we present many cases of retinal damage caused by laser pointers in patients who visited our clinic over the past year (from January 2024 to January 2025). Results: We discuss the clinical presentation, diagnostic findings, management, and outcomes of 32 patients with laser-induced retinal damage. Our findings highlight variable recovery patterns depending on injury severity, ranging from spontaneous resolution in some patients to complications requiring intervention in others. Conclusion: This study explored the potential visual damage caused by laser pointers and provided recommendations for safe usage.